Changes in coastline and coastal reclamation in the three most developed areas of China, 1980–2018. (15th April 2021) - Wang, Xuege; Yan, Fengqin; Su, Fenzhen
Abstract: With dramatic coastline changes, developed coastal areas in China are seldom detected and compared in detail regarding the spatiotemporal evolution of coastline migration and coastal reclamation. This study detected and compared the spatiotemporal changes in coastline and coastal reclamation in three developed coastal areas: the Bohai Bay-Yellow River Estuary Zone (BHB-YREZ), the Yangtze River Estuary-Hangzhou Bay Zone (YRE-HZBZ) and the Pearl River Estuary Zone (PREZ). Landsat images from 1980, 1990, 2000, 2010 and 2018 were employed to derive the coastline and reclamation information for the three coastal areas. The ecological risk index was applied to explore the ecological risk characteristics of land use change in the reclamation areas. The results showed that the length of the coastlines in the BHB-YREZ, YRE-HZBZ and PREZ increased from 717.6 km, 716.3 km, and 519.6 km in 1980 to 1252.8 km, 822.6 km and 780.9 km in 2018, with annual change rates of 14.1 km/year, 2.8 km/year and 6.9 km/year, respectively. 91.0%, 97.8%, 84.5% of the coastline in the BHB-YREZ, YRE-HZBZ and PREZ was artificial coastline by 2018, respectively. From 1980 to 2018, the total reclamation areas in the BHB-YREZ, YRE-HZBZ and PREZ were 2531.4 km 2, 1145.5 km 2, and 769.2 km 2, respectively. After 2000, except for agricultural land and aquaculture ponds, ports, construction land and tied islands were the main reclaimed types in the BHB-YREZ, YRE-HZBZ and PREZ, respectively. The overall ecological risk in the BHB-YREZ showed an increasing tendency during the past four decades, while in the YRE-HZBZ and PREZ, it rose from 1980 to 1990 to 2000–2010, and declined in 2010–2018. Coastal reclamation activities, especially construction land or ports, should be strictly and scientifically planned to protect the coastal environment. Graphical abstract: Image 1 Highlights: ● The spatiotemporal changes in coastline and coastal reclamation in three developed coastal areas of China from 1980 to 2018 were studied. ● The length of coastline in the three coastal zones presented a considerable growth during the study period. ● The main reclaimed types transferred from agricultural land and aquaculture ponds to construction land or ports in the past four decades. ● The ecological risk in the three study areas showed an overall increasing trend.